Production of Shallots (Allium ascalonicum L. var. bauji) with The Provision of Liquid Organic Fertilizer Mixed Pineaplle Peel Waste (Ananas comosus L.) and Water Hyacinth (Eichornia crassipes L.) - Ruth Isabella Elisabeth Sari Mutiara Sianturi; Mukarlina Mukarlina; Zulfa Zakiah (Jurnal Biologi Tropis, 2023)
Red onion is a rural commodity developed by people in West Kalimantan. The development of shallots in West Kalimantan is mostly completed in the formation of media in the form of peat soil with physical and substantive qualities that are unfit for the production of shallots. The application of Liquid Organic Fertilizer (LOF) is one method used to overcome the limitations of shallot cultivation on peatlands. The aim of the study was to determine the production of shallots of the Bauji variety influenced by a mixture of liquid organic fertilizer containing waste pineapple skin and water hyacinth. The study used an experimental method with a completely randomized design (CRD) and there were seven treatment standards for liquid organic fertilizer. The results of the study found that liquid organic fertilizer mixed with water hyacinth waste and pineapple peel had an effect on tuber wet weight, tuber dry weight, tuber number and tuber diameter. The best concentration is on. LOF treatment of 50 ml/L to increase the production of shallots of the bauji variety planted on peatlands in West Kalimantan. This treatment resulted in the highest tuber wet weight value of 55.07 grams and tuber dry weight of 15.22 grams, the number of tubers was 8 pieces and the tuber diameter was 2.44 cm.